ESTRATEGIAS PARA O DESENVOLVIMENTO DA UNIJUI-CAMPUS SANTA ROSA DIANTE DO CENARIO ATUAL - DALLALBA, DANIEL; SANTOS, JAIR L. D.; BÜTTENBENDER, PEDRO L.; WAGNER, ADRIANO (Salão do Conhecimento, 2013)
Resumo